IMPROVING PHOTOVOLTAIC MODULE PERFORMANCE WITH PASSIVE COOLING USING WATER FLUID - Virgin Supit, Marshall
The decrease in the efficiency of photovoltaic modules due to high temperatures has become a major problem affecting system performance. This study aims to optimize the solar photovoltaic system through a passive cooling method using adjustable water flow on the surface of the photovoltaic modules to reduce the panel temperature, improve the energy conversion efficiency, and measure the energy savings achieved. By analyzing key parameters such as temperature and irradiance, this study models the effect of temperature on the performance of photovoltaic cells. It investigates how temperature control can affect the overall system efficiency by simulation using Computational Fluid Dynamics (CFD) ANSYS 2024 R1. The results show that increasing the coolant's mass flow rate significantly improves the cooling system's efficiency on the photovoltaic module. The cooling system's relative efficiency increases with the mass flow rate increase. At irradiance of 1,200 W/m2, the relative efficiency at a flow rate of 0.05 kg/s is 1.03%, rising to 6.04% at a flow rate of 0.25 kg/s, indicating a positive effect of the cooling system on the temperature of the photovoltaic module. The water inlet temperature also plays an important role in the cooling system's efficiency. A lower inlet temperature (21°C) was more effective in maintaining low panel temperature than a higher inlet temperature (23°C or 25.12°C), especially under high irradiance conditions. The power saving analysis showed that the efficiency of the cooling system is highly dependent on a combination of variables such as irradiance, head pump, and water flow rate. Significant power saving was recorded at high irradiance (1,100 - 1,200 W/m2) and low head (2.5 - 5 meters). The cooling system remained effective in generating positive power savings despite the decrease in the temperature coefficient of the photovoltaic module. Conversely, increasing the temperature coefficient improved the performance of the cooling system. This study indicates that the cooling system can significantly increase the efficiency of photovoltaic modules by minimizing excess temperature on the panels, and generating energy savings, especially under the combination of high irradiance,